Characterization of Cases of Negligence Type Violence against Children in a State of Brazil - Andressa Aya Ohta; Laura Akemi Storer Makita; Herbert Leopoldo de Freitas Goes (Research Highlights in Disease and Health Research Vol. 5, 2023)
Neglect is a scenario present in the lives of many children in the country, becoming a public health problem of concern. Given the indicators about neglect, it is essential to know the characteristics of cases, in order to understand and promote actions to prevent the event. Objective: To analyze the characteristics of the notifications of interpersonal/self-inflicted violence of neglect with children in the state of Paraná. Methods: epidemiological descriptive study with a quantitative approach on the characterization of the notifications of neglect with children in the period from 2017 to 2021 in the state of Paraná. The data were obtained from the Notification Form of Interpersonal and Self-Provoked Violence that are registered in the Information System of Notification Aggravities. For this study, we analyzed the cases of negligence violence against children aged between 1 and 9 years old. Since this was a study that used public domain records, ethical approval was waived. Results: We analyzed 22.341 notifications, mostly males, between 1 and 4 years old, of white race/color. The main means of aggression was poisoning/intoxication and the main responsible parties were the mother and father. There was an increase in cases in 2018, compared to the previous year, following with an increase in 2019, presenting a significant drop from 2020 and in 2021. Conclusion: Violence of the negligence type in Paraná proved to be a significant grievance for children. The fact that parents are the most responsible for the neglect of children raises reflection about families, not being able to classify them.